A Comment on Wu, Zhang, Wang (2023) - Alejandro Abarca; Felipe Juan; Ke Lyu; Alexa Prettyman; Idil Tanrisever (Institute for Replication (I4R), 2024)
Wu et al. (2023) estimate the effect of classroom seating arrangements in China using a randomized control trial with two treatment schemes. The first treatment scheme involves seating high and low achieving students together, and the second treatment involves this same seating arrangement with financial incentives for the high-achieving students, if their deskmates' test scores improved. All statistically significant impacts come from the incentivized treatment scheme. Wu et al. (2023) find that low-achieving students sitting next to incentivized high-achieving students perform 0.24 SD (p-value=0.018) better on math exams. In addition, being assigned to the incentive treatment scheme increased extraversion and agreeableness for low and high achieving students. Lastly, they do not find much evidence of peer effects on test scores nor personality traits. This study is computationally reproducible using their provided replication package. We ran their code using Stata 14, 17, and 18. After running their replication package, we further investigated Tables 2-5. The main conclusions are generally robust to various coding decisions. Notably, in investigating the peer effects, when we change the specification to also control for the difference in baseline scores between the student and their deskmate, we find that the more dissimilar deskmates are at baseline, the bigger the peer effects.
Keywords: 330